2019
DOI: 10.1111/tid.13119
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and successful containment of a carbapenem‐resistant Enterobacteriaceae outbreak in a Southern Italian Transplant Institute

Abstract: Introduction: Carbapenem-resistant enterobacteriaceae (CRE) infections are difficult to treat and pose a serious threat to solid organ transplant (SOT) recipients. At our institute we observed an infection burden in 2012. Methods:In order to contain the spread of CRE infections, we established a taskforce to implement guidelines suggested by the Centers for Disease Control and Prevention (CDC) for this type of outbreak. Here, we describe the epidemiology of the outbreak in our SOT population, and the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…However, the continual use of carbapenems and polymyxins to treat bacterial infections resistant to penicillins, cephalosporins, and carbapenems is increasing the rate of resistance to these last‐resort antibiotics 2,4,9,11 . The emergence of carbapenem‐resistant (CR) and/or polymyxin‐resistant (PR) MDR infections is thus limiting therapeutic options and increasing hospital stay, healthcare costs, morbidity, and mortality 12–14 . Subsequently, the WHO has classified CR Gram‐negative bacteria (CR‐GNB) as critical priority pathogens for which novel antibiotics are urgently needed 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…However, the continual use of carbapenems and polymyxins to treat bacterial infections resistant to penicillins, cephalosporins, and carbapenems is increasing the rate of resistance to these last‐resort antibiotics 2,4,9,11 . The emergence of carbapenem‐resistant (CR) and/or polymyxin‐resistant (PR) MDR infections is thus limiting therapeutic options and increasing hospital stay, healthcare costs, morbidity, and mortality 12–14 . Subsequently, the WHO has classified CR Gram‐negative bacteria (CR‐GNB) as critical priority pathogens for which novel antibiotics are urgently needed 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, preventing colonization/infection of ICU patients in a ward where exposure from other patients is major can be viewed as an achievement of a great importance. Even though this was not a case control study and the number of patients was limited, there is lack of information regarding risk factors, antibiotic use, and prior hospital stay in patients admitted to (6)(7)(8)(9). In contrast, data are limited for developing countries.…”
mentioning
confidence: 99%
“…National and global institutions have provided several recommendations for reducing CRKP incidence, including active surveillance, hand hygiene (HH), contact precautions (CP), and terminal disinfection. Various studies have been conducted to confirm the effectiveness of different IPC interventions for decreasing the CRKP incidence rate (9)(10)(11)(12)(13)(14). Our previous study also showed that comprehensive IPC interventions, including de-escalation and targeted bundles, significantly reduced the incidence of CRKP colonization/infection (4).…”
Section: Introductionmentioning
confidence: 81%